PENGGUNAAN INDIRECT EVIDENCE (ALAT BUKTI TINDAK LANGSUNG) OLEH KPPU DALAM PROSES PEMBUKTIAN DUGAAN PRAKTIK KARTEL (STUDI DI KANTOR KOMISI PENGAWAS PERSAINGAN USAHA WILAYAH I MEDAN) - Martono Anggusti; Dina Mayasari Sinaga; Janpatar Simamora (Magister Hukum Universitas HKBP Nommensen, 2021)
Provisions regarding business competition law in Indonesia are regulated in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition which regulates various prohibitions on actions that cause unfair business competition from activities or agreements between business actors, one of which is cartels. This study aims to analyze the use of indirect evidence by KPPU in the process of proving allegations of cartel practice and to analyze the factors that hamper the use of indirect evidence by KPPU in the process of proving alleged cartel practices. The use of research as a contribution to knowledge in the field of legal science, especially business competition law related to indirect evidence in cartel evidence and to add insight to legal practitioners, legal consultants, especially in the field of law regarding indirect evidence by the KPPU. This research is a normative legal research using the approach method in this research is a statutory approach and a case approach.